Meningkatkan Kejujuran Akademik Mahasiswa Melalui Konseling Kelompok Values Clarification - Gunawan, I Made Sonny (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
The purpose of this study is to emphasize the effectiveness of group calrification counseling in modeling techniques for the academic honesty of students. This study uses a repetead measure experimental design with a pretest and multiple posttest design. The subjects in this study were 12 students in one private university, the city of Mataram. Data were collected using an academic honesty scale. Data analysis used repeated measure ANAVA statistics. The results of this study reveal that group counseling values clarification with modeling techniques effective to improve student academic honesty. As for the level of academic honesty of students viewed from gender there is no significant difference.Â